Clinician Perspectives of Barriers in Perinatal Palliative Care. Issue 1 (January 2015) - Wool, Charlotte
Abstract Purpose: Perinatal palliative care (PPC) is a developing model of care aimed at providing supportive services to families anticipating fetal or neonatal demise. This study measured barriers physicians and advance practice nurses report in providing and referring patients to PPC. Study Design and Methods: A cross-sectional survey design using the Perinatal Palliative Care Perceptions and Barriers Scale © was administered using a Web-based tool. Recruitment was completed via email and flyer invitations and list serves. Physicians (n = 66) and advance practice nurses (n = 146) participated. T-test and Mann-Whitney U were used to examine differences in clinician-reported barriers to PPC. Results: Physicians and nurses differ significantly in the barriers they report. Nurses expressed more obstacles at the healthcare systems level reporting difficulty in their ability to garner interdisciplinary support and gain administrative backing. Physicians are more confident in their ability to counsel patients than nurses. Members of both disciplines express similar feelings of distress and helplessness when caring for families expecting a fetal or neonatal demise. They also report a lack of societal support and understanding about PPC. Clinical Implications: Cultivating an environment of collaboration and interdisciplinary communication can benefit both caregivers and patients. Nurses have an opportunity to lead and promote PPC endeavors through participating in advantageous partnerships and research. Both disciplines may benefit from interventions directed at increasing their comfort in caring for patients in a palliative setting through targeted education and supportive staff services.